2014
DOI: 10.37237/050102
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Picture: A Preliminary Investigation into Experts’ Beliefs about the Roles and Purposes of Self-Access Centres

Abstract: This paper presents results from phase one of a large-scale, two-phase research project investigating self-access centre (SAC) experts’ (Centre Directors; Centre Managers; Centre Coordinators; Learning Advisors) beliefs about the roles and purposes of SACs. The project adopts both the fundamental assumptions and approaches of learner belief studies in SLA and teacher cognition research in education. However, it examines neither learners nor teachers; instead, all the participants are SAC practitioners. Phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In Navarro's (2014) Navarro's finding that the SAC managers confirmed the importance of providing access to 'target culture contact' and 'successful language users' is particularly interesting in relation to this study; these are things which Room 101 and other social learning SACs do through interaction-based activities.…”
Section: Different Sac Models In Uk Hementioning
confidence: 73%
See 2 more Smart Citations
“…In Navarro's (2014) Navarro's finding that the SAC managers confirmed the importance of providing access to 'target culture contact' and 'successful language users' is particularly interesting in relation to this study; these are things which Room 101 and other social learning SACs do through interaction-based activities.…”
Section: Different Sac Models In Uk Hementioning
confidence: 73%
“…To what extent is Room 101's social learning approach used in other UK HE SACs? Navarro (2014), when looking at different SACs, found that "there exists an array of mission statements, principles, descriptions of services, and outlines of goals and objectives. I was left with a highly eclectic picture of SACs."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To promote students' ownership of the Centre, their use of English, and learner autonomy (as in Heigham, 2011, Malcolm, 2011, and Navarro, 2014, apart from giving workshops and consultations, the Centre could recruit a volunteer team comprising students who are keen to help out with daily administration and maintenance of the SALL's resources. The benefit is mutual; students will have more exposure to English as they will be required to interact in English at the SALL while providing the SALL with a greater human resource.…”
Section: Suggestions For Developmentmentioning
confidence: 99%
“…Yet, it is interesting to note that required use of SACs appears quite prevalent. Indeed, Navarro (2014) surveyed 38 self-access experts from various self-access centres regarding their beliefs about the purposes of self-access centres and found that "61% reported mandatory SAC attendance" (p. 15). When the experts were asked if they believed SAC use should not be required, only 16% responded that voluntary use was essential with 58% stating that such use was preferable, and 26% saying it should be compulsory.…”
mentioning
confidence: 99%